منهج الشيخ البشير الإبراهيمي في الدعوة إلى الله من خلال مقالته في جريدة البصائر - دراسة تحليلية - لعمارة, خديجة (University of Eloued جامعة الوادي, 2017)
تناولت هذه الدراسة موضوع منهج الشيخ محمد البشير الإبراهيمي في الدعوة إلى الله من خلال مقالاته في جريدة البصائر، وقد هدفت هذه الدراسة إلى التعريف بعلم من أعلام الجزائر، ألا وهو الشيخ الإبراهيمي وبيان منهجه في الدعوة إلى الله وذلك من خلال مقالاته في جريدة البصائر معتمدة في ذلك على المنهج التاريخي، والمنهج الوصفي التحليلي. وقد توصلت الدراسة إلى جملة من النتائج أهمها: 1- يمثل الشيخ الإبراهيمي بإنتاجه الفكري والثقافي المتنوع والشامل، وبعمله الدعوي المنظم والمستمر، وبجهوده الإصلاحية في مختلف الميادين مدرسة كاملة، وتجربة غنية وفذة. 2- أن معالم الفكر التربوي عند الإبراهيمي تمتاز بالنظرة الثاقبة والشمولية، إذ يعتبر فكره نموذجا تربويا مميزا، إذ لم يكن الشيخ مصلحا ومرشدا فحسب بل كان مفكرا ومنظرا في مجال التربية والتعليم حيث سعى إلى وضع خطة تربوية متدرجة، محسوبة ومستوفية العناصر شملت المعلم والمتعلم والمنهج أو الطريقة والمدرسة. 3- تتمثل فلسفة الإصلاح عند الإبراهيمي في محورين كبيرين هما الإصلاح الديني وذلك من خلال إرجاع المسلمين إلى كتـاب ربهم وسنـة نبيهـم وربطهـم بسلفهم الصـالح، والإصلاح الاجتماعي وذلك من خلال عرضه للمشاكل الاجتماعية التي تمس الحياة اليومية مسا مباشرا، وتشخيص العلاج لها. وهو يرى أنه هناك تلازم ضروري بينهما لتحقيق النهوض بالبلاد ثقافيا واجتماعيا. ومن أهم ما توصي به هذه الدراسة ما يلي: 1- ضرورة الاستفادة من الفكر التربوي للشيخ الإبراهيمي في إقامة منهاج تربوي جديد. 2- أن يختار رجال التربية من كتابات الشيخ الإبراهيمي نصوصا تدرس في جميع مراحل التعليم من الابتدائي إلى الثانوي إلى العالي. 3- أن يوجه طلبة العلم إلى القيام برسائل متخصصة في كل ناحية من نواحي نبوغه العام. This study dealt with the subject of the approach of Sheikh Mohammed Al-Bashir Al-Ibrahimi in the call to God through his articles in Al-Busayer newspaper. This study aimed to introduce a scholar of the Algerian scholars, namely Sheikh Brahimi and his method of calling to God through his articles in Al-Bassair in which it relied on the historical approach, and descriptive analytical approach. The study reached a number of results, the most important of which are: 1- Sheikh Brahimi represents with his diverse intellectual and cultural production, his systematic and continuous work, his reform efforts in various fields, a complete school and a rich and unique experience. 2 - The features of educational thought at Brahimi have a strong insight and comprehensiveness, as his thought is considered as a distinctive educational model, as the Sheikh was not only a reformer and mentor, but was a thinker and perspective in the field of education, where he sought to develop a gradual educational plan, calculated and satisfied elements included the teacher and the learner and the curriculum or the method and the school. 3. The philosophy of reform in Brahimi is two major axes: religious reform through the return of Muslims to the book of their Lord and the Sunnah of their Prophet, and linking them to their good predecessors and social reform by presenting social problems affecting daily life directly and diagnosing treatment for it. He believes that there is a necessary correlation between them to achieve the cultural and social advancement of the country. The most important recommendations of this study are: 1 - the need to benefit from the educational thought of Sheikh Brahimi in the establishment of a new educational curriculum. 2 - Men of education should choose from the writings of Sheikh Brahimi texts to be taught at all stages of education from primary to secondary to higher education. 3 - to direct knowledge students to carry out specialized messages in every aspect of his general prophecy.
مذكرة ماستر تخصص دعوة واعلام
Keywords: الدعوة، محمد البشير الإبراهيمي، الإصلاح، جمعية العلماء المسلمين الجزائريين، الحركة الإصلاحية; Al-Daawa, Muhammad al-Bashir al-Ibrahimi, Islah, Association of Algerian Muslim Scholars, Reform Movement, Al-Busayer Newspaper